PENGARUH FINANCIAL LITERACY DAN FINANCIAL ATTITUDE TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PENDIDIKAN AKUNTANSI UNNES 2022 DENGAN PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) SEBAGAI VARIABEL INTERVENING - Aziz, Afdelfan Nurol; Fatimah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of financial literacy and financial attitude on financial management behavior among Accounting Education students of Universitas Negeri Semarang class of 2022, with financial technology (fintech) as an intervening variable. This research employed a quantitative descriptive approach using Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis through SmartPLS software. The population of this study consisted of 169 Accounting Education students, with 119 respondents selected using the Slovin formula. Data were collected through questionnaires distributed to active students. The results showed that financial literacy and financial attitude had a positive and significant effect on students’ financial management. In addition, financial literacy and financial attitude also had a positive and significant effect on the use of fintech. Fintech was proven to have a positive and significant effect on financial management and was also able to mediate the relationship between financial literacy and financial attitude toward financial management behavior. These findings indicate that improving financial literacy and financial attitude, supported by the utilization of fintech, can strengthen students’ ability to manage their finances effectively in the digital era.